Maximal static and dynamic neck strength in hockey players and wrestlers - Broennle, M.; Kivi, D.; Zerpa, C. (International Journal of Sports Science, 2017)
The purpose of this study was to compare maximal static and dynamic neck strength between hockey players and wrestlers. Athletes were recruited from the university men`s hockey and wrestling teams, with active male university students serving as a control group. Each group consisted of eight participants between the ages of eighteen and twenty-four. Anthropometric measurements, including height, mass, neck length, and neck girth were taken prior to testing. Static and dynamic cervical strength testing was completed using a modified Nautilus neck strengthening machine. Maximal static neck flexion and extension strength were measured using a load cell attached to the arm of the Nautilus machine, which was set in a neutral neck position. To measure dynamic neck strength, a 6-Repetition Max (RM) submaximal test was completed for cervical flexion and extension, from which 1-RM values were predicted. Mean normalized strength values were significantly higher among all participants for neck extension (M = .32, SD = .12) than for neck flexion (M = .20, SD = .07). Mean neck strength was significantly greater for dynamic muscle contractions (M = .31, SD = .13) than for static muscle contractions (M = .22, SD = .08). When comparing among groups, mean normalized static neck strength of the wrestlers was significantly greater than that of the hockey players in both the flexion and extension directions, with no differences seen between the hockey players and the controls. Differences in static and dynamic neck strength between hockey players and wrestlers are likely associated with the demands of each sport and their sport-specific strength training.